2019
DOI: 10.1016/j.ptsp.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting knee abduction during weight-bearing activities in individuals with anterior cruciate ligament reconstruction

Abstract: ObjectiveTo investigate if muscle strength and muscle activation patterns are associated with increased knee abduction during two functional tasks, commonly used in rehabilitation for individuals with anterior cruciate ligament reconstruction (ACLR). Design Cross-sectional study Setting LaboratoryParticipants 24 women and 29 men approximately 7 months after ACLR. Main Outcome MeasuresIsometric peak torque of the trunk and lower extremity muscles were determined during maximal voluntary contractions. Trunk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…6,14,69 However, based on our findings, no significant varus rotation was detected in either operative group during the lunge motion because the strength of the knee and trunk muscles could be restored better 1 year after surgery with appropriate rehabilitation, which contributed to knee varus-valgus rotation changes to a nearly normal status. 12 The potential onset of osteoarthritis via an altered knee varus-valgus profile might be correspondingly reduced over time.…”
Section: Discussionmentioning
confidence: 99%
“…6,14,69 However, based on our findings, no significant varus rotation was detected in either operative group during the lunge motion because the strength of the knee and trunk muscles could be restored better 1 year after surgery with appropriate rehabilitation, which contributed to knee varus-valgus rotation changes to a nearly normal status. 12 The potential onset of osteoarthritis via an altered knee varus-valgus profile might be correspondingly reduced over time.…”
Section: Discussionmentioning
confidence: 99%
“…Slater et al [91] pointed out that the peak knee flexion angle was smaller and the peak knee adduction angle was greater for the ACL injury patients in walking. Cronstrom et al [92] represented that the knee adduction degree during weight-bearing activities for ACLinjured patients was greater in walking. Gao and Zheng [93] indicated that the ACL-injured patients had slower speed and smaller stride length during walking.…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Cronström et al reported that lower knee muscle strength and lower muscle activation of the trunk was associated with increased 3D knee abduction in women, but not in men. 10 While there is some understanding of the sex differences and modifiable factors associated with knee abduction (one aspect of postural orientation), 9 36 further studies are needed to investigate underlying modifiable factors for other POEs, for example, muscle strength and muscle activation patterns, in men and women. Such information may help design rehabilitation programmes aimed at improving postural orientation in men and women after an ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…8 Thus, it is of importance to investigate sex differences in various measures of postural orientation, to guide rehabilitation progression for men and women, respectively. A systematic review 9 and recent crosssectional study 10 observed worse postural orientation, that is, greater 3D knee abduction angle, in both women with an ACL injury and healthy women, compared with men. In contrast, no sex differences were observed for visual assessment of Knee Medial-to-Foot Position (KMFP).…”
Section: Open Accessmentioning
confidence: 98%
See 1 more Smart Citation